1988
DOI: 10.2307/3282485
|View full text |Cite
|
Sign up to set email alerts
|

Eimeria maxima (Apicomplexa): A Comparison of Sporozoite Transport in Naive and Immune Chickens

Abstract: This study compared the early stages of infection in naive and immune chickens infected with Eimeria maxima. An immunoperoxidase stain was developed and used to detect sporozoites and early schizonts in tissue sections of intestinal epithelium. A significantly higher proportion of sporozoites was present in the crypts of naive chickens, 48 hr postinoculation of oocysts, compared to immune chickens. Sporozoites in immune birds tended to remain in the lamina propria rather than migrate to the crypts. Sporozoites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 15 publications
3
23
0
Order By: Relevance
“…Their experiments showed that this effect was due, at least partially, to the failure of sporozoites transported by IELs to be transferred to crypt enterocytes. Riley and Fernando (1988) found that in immune birds, as compared to nonimmune, a significantly greater number of IELs harbouring sporozoites of E. maxima tended to remain in the lamina propria rather than to migrate to the crypts.…”
Section: Immunity and Migration Of Sporozoitesmentioning
confidence: 95%
“…Their experiments showed that this effect was due, at least partially, to the failure of sporozoites transported by IELs to be transferred to crypt enterocytes. Riley and Fernando (1988) found that in immune birds, as compared to nonimmune, a significantly greater number of IELs harbouring sporozoites of E. maxima tended to remain in the lamina propria rather than to migrate to the crypts.…”
Section: Immunity and Migration Of Sporozoitesmentioning
confidence: 95%
“…Because of the small size of the fish, whole heart, stomach, and small and large intestine were sampled from five fish at 1, 2,4,8,12,18,24,30,36,42,48,60, and 72 hours PE and 4, 5, 6, and 7 days PE. Every sample was fixed in 4% paraformaldehyde (Sigma) in phosphate-buffered saline (PBS) for 40 minutes at room temperature and then stored at 5 C in 70% ethanol until processed further.…”
Section: Fish Infection and Samplingmentioning
confidence: 99%
“…In E. maxima-immune birds, inhibition of sporozoite transport from the LP to the crypts was reported (Riley & Fernando, 1988). In the case of E. tenella, however, sporozoite transfer from IEL to crypt enterocytes rather than sporozoite transport, is inhibited (Rose et al, 1984c).…”
Section: Sporozoite Invasion and Transportmentioning
confidence: 99%
“…Eimeria vermiformis has been transmitted to uninfected mice by feeding them blood or homogenized lung or liver tissue, but not spleen, from infected mice at 1, 2 and 3 dpi (Ball et al, 1990). Transfer of coccidia between chickens is also possible by feeding blood or homogenates of lung, liver, or heart tissue and, less consistently, spleen, from infected birds at 3 and 4 dpi to uninfected recipients -, Riley & Fernando, 1988. Parenteral administration of oocysts or sporozoites results in the typical intestinal infections (Ball et al, 1989).…”
Section: Extra-intestinal Stages Of Coccidiamentioning
confidence: 99%